A good student subject: a Foucauldian discourse analysis of an adolescent writer negotiating subject positions - Worthman, Christopher; Troiano, Beverly (Critical studies in education, 2019)
In this article, we draw on the work of Michel Foucault to analyze one student's subject development in an expository writing classroom. James, the participant, was embarking on the project of becoming a good student, as he understood it, after struggling and leaving school previously. Drawing on interviews, classroom observations and written artifacts, we use Foucauldian concepts and discourse analysis, along with one James Gee's discourse analysis tools - the identities building tool - to conduct a microanalysis of James's efforts to objectify himself as a good student subject. The data show how James acquiesced to the truths and practices of the regime of school, including how he mobilized truths of the regime through a process we call masked confession. That is, he negotiated his good student subject position by masking or silencing other subject positions. James's masked confession was his way of negotiating the realm of 'multiple truths,' or multiple subject positions.